Welcome to Westonci.ca, the ultimate question and answer platform. Get expert answers to your questions quickly and accurately. Connect with a community of experts ready to help you find accurate solutions to your questions quickly and efficiently. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
3x+(1/14)= 2x/8
24x+(4/7)=2x ( i multiplied everything by 8)
22x+4/7=0 ( i subtracted 2x to both sides)
22x= -4/7 ( i subtracted 4/7 to both sides)
x= (-4/7)/ 22
x= -2/77
24x+(4/7)=2x ( i multiplied everything by 8)
22x+4/7=0 ( i subtracted 2x to both sides)
22x= -4/7 ( i subtracted 4/7 to both sides)
x= (-4/7)/ 22
x= -2/77
[tex]3x + \frac{1}{14} = \frac{2x}{8} [/tex]
First, you multiply everything by 8, so you get:
[tex] 8(3x + \frac{1}{14}) = 8( \frac{2x}{8})[/tex]
Then, you develop, and you get:
[tex]24x + \frac{8}{14} = 2x[/tex]
You simplify [tex] \frac{8}{14} [/tex] by dividing by 2, and you get:
[tex]24x + \frac{4}{7} [/tex] = 2x
Then, you put known numbers apart (numbers without x), and unknown numbers apart (numbers with x), which means you move 2x to the other part (and it become -2x), and [tex] \frac{4}{7} [/tex] to the other part ( and it become [tex]- \frac{4}{7} [/tex]), so you get:
[tex]24x - 2x = - \frac{4}{7} [/tex]
you subtract and you get:
[tex]22x = - \frac{4}{7} [/tex]
then, you move 22 to the other part, and since it's a multiplication, it become a division, so you get:
[tex]x = \frac{ - \frac{4}{7} }{22} [/tex]
As you know, [tex]22 = \frac{22}{1} [/tex], and dividing 2 fraction is equal to multiplying the first fraction by the inverse of the second fraction, so you get:
[tex] -\frac{4}{7} * \frac{1}{22} = x[/tex]
You multiply and you get:
[tex] - \frac{4}{154} = x[/tex]
4 and 154 have a common factor which is 2, so you divide each one by 2, and you get:
[tex] -\frac{4/2}{154/2} = x[/tex]
you divide, and you get:
[tex] -\frac{2}{77} = x[/tex]
So, [tex]x = -\frac{2}{77} [/tex]
Hope this Helps! :D
First, you multiply everything by 8, so you get:
[tex] 8(3x + \frac{1}{14}) = 8( \frac{2x}{8})[/tex]
Then, you develop, and you get:
[tex]24x + \frac{8}{14} = 2x[/tex]
You simplify [tex] \frac{8}{14} [/tex] by dividing by 2, and you get:
[tex]24x + \frac{4}{7} [/tex] = 2x
Then, you put known numbers apart (numbers without x), and unknown numbers apart (numbers with x), which means you move 2x to the other part (and it become -2x), and [tex] \frac{4}{7} [/tex] to the other part ( and it become [tex]- \frac{4}{7} [/tex]), so you get:
[tex]24x - 2x = - \frac{4}{7} [/tex]
you subtract and you get:
[tex]22x = - \frac{4}{7} [/tex]
then, you move 22 to the other part, and since it's a multiplication, it become a division, so you get:
[tex]x = \frac{ - \frac{4}{7} }{22} [/tex]
As you know, [tex]22 = \frac{22}{1} [/tex], and dividing 2 fraction is equal to multiplying the first fraction by the inverse of the second fraction, so you get:
[tex] -\frac{4}{7} * \frac{1}{22} = x[/tex]
You multiply and you get:
[tex] - \frac{4}{154} = x[/tex]
4 and 154 have a common factor which is 2, so you divide each one by 2, and you get:
[tex] -\frac{4/2}{154/2} = x[/tex]
you divide, and you get:
[tex] -\frac{2}{77} = x[/tex]
So, [tex]x = -\frac{2}{77} [/tex]
Hope this Helps! :D
We appreciate your time. Please come back anytime for the latest information and answers to your questions. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.